Model Permintaan Beras Giling Lokal oleh Masyarakat di Kota Kupang, Provinsi Nusa Tenggara Timur - Marince P. Tunardjo (Balitbangda Provinsi Lampung, 2017)
The research was conducted in Kupang district from February November 2013. The data collection methods used were interview and record technique through observation on 115 people. Technique of data analysis was descriptive and multiple regression was done to resolve the second goal. The results of this research were (1) milled rice demand was influenced jointly by local milled rice, the price of imported rice, the number of constumers, the expenditures on advertising, the product attributes, the consumer taste and income; (2) variable of import price significantly affected the demand for imported rice at 99 % confidence level, and the variable of the local milled rice price, the number of consumers, the product attributes and the expenditures for advertising affected on the level of 90 %. The variable of consumer taste and incomewerenot significant because (1) public income of the City of Kupang was low so the need for rice was restricted by cash held; (2) the average consumersearned as civil servants with meager salary they werefocus on consuming rice ration while the community who were not civil servants consumed other low-price rice; and (3) people did not give priority to the taste of varieties of rice because of the limited abilityon the taste of varieties of rice in the market.